Penentuan Kekerasan dan Struktur Mikro Sambungan Las Baja Karbon Rendah Akibat Perlakuan Las Titik - Edison Sihombing (Institut Teknologi Bandung, 2002)
Research on the effect of spot welding parameters on hardness and microstructure of low carbon steel weld joints has been done. The research was focused on determining the combination of welding parameters to get the best welding result. In this research, the thickness of plate used are: 1 mm and 3 mm. For the plate thickness of 1 mm, the currents applied are 2 kA, 4 kA, 6 kA, 8 kA, and 10 kA, electrode forces are 2 kN, 2.4 kN, 2.8 kN, 3.2 kN, and 3.6 kN and welding times are 20 seconds, 30 seconds, 40 seconds, 35 seconds, 40 seconds, and 45 seconds. For the plate thickness of 3 mm, the currents applied are 8 kA, 9 kA, 10 kA, 11 kA, and 12 kA, electrode forces are 2 kN, 2.4 kN, 2.8 kN, 3.2, kN and 3.6 kN and welding times are 20 seconds, 30 seconds, 40 seconds, 50 seconds, and 57 seconds. Tests of mechanical properties performed include hardness using the Vickers method, weld shear strength using stretching test whereas metallurgical test was performed using optical microscope. Welding process shows no weld joint for the plate thickness of 1 mm, if the current is less than 4 kA. If the current is less than 8 kA there is no weld joint for the plate thickness of 3 mm. Hardness test results showed that the higher the current, welding time, and electrode force, the harder the metal. This phenomenon occurs since higher welding variables can cause recrystallization and change the phase of metal that heighten the hardness of metal. Microstructure test results showed that the material contains ferrite, pearlite, and martensite. As a final result it can be concluded that for 1 mm plate the best combination of variables is 6 kA of current, 30 seconds of welding time and 2 kN of electrode force, and for 3 mm plate is 10 kA of current, 20 seconds of welding time, and 3.6 kN of electrode force.